Determinan Tingkat Kemiskinan Di Indonesia - Setiawan, Prayoga; Muchtar, Masruri; Sihombing, Pardomuan Robinson (PT WIM Solusi Prima, 2024)
Poverty is a problem in the development process in most countries, especially in developing countries such as Indonesia. Analyzing the factors that influence poverty is important in formulating effective and targeted policies. This study aims to analyze the independent variables of village funds, unemployment rate, human development index (HDI), and gross regional domestic product (GRDP) affecting the dependent variable of the number of poor people in Indonesia in 2022. The study used the Ordinary Least Square (OLS) model to analyze cross-section data from 34 provinces in Indonesia in 2022. The results show that village funds and GRDP have a significant positive influence on the number of poor people, but HDI and unemployment rate do not have a significant influence. The findings make a significant contribution to understanding the factors that contribute to the poverty rate in Indonesia, as well as providing a basis for formulating more effective development policies to reduce the poverty rate in the future.